Electric dipole moments in a leptoquark scenario for the B-physics anomalies - Wolfgang Altmannshofer (Journal of High Energy Physics, 2020)
Abstract Vector leptoquarks can address the lepton flavor universality anomalies in decays associated with the b → cℓν and b → sℓℓ transitions, as observed in recent years. While not required to explain the anomalies, these leptoquarks generically yield new sources of CP violation. In this paper, we explore constraints and discovery potential for electric dipole moments (EDMs) in leptonic and hadronic systems. We provide the most generic expressions for dipole moments induced by vector leptoquarks at one loop. We find that O(1) CP-violating phases in tau and muon couplings can lead to corresponding EDMs within reach of next-generation EDM experiments, and that existing bounds on the electron EDM already put stringent constraints on CP-violating electron couplings.